A genome wide pattern of population structure and admixture in Peninsular Malaysia Malays - Wan Isa, Hatin; Ab Rajab, Nur Shafawati; Etemad, Ali; Jin, Wenfei; Qin, Pengfei; Xu, Shuhua; Jin, Li; Tan, Soon Guan; Limprasert, Pornprot; Feisal, Merican Amir; Idid, Mohammed Rizman; Alwi, Zilfalil; et al. (Springer, 2014)
Background: The Malays consist of various sub-ethnic groups which are believed to have different ancestral origins based on their migrations centuries ago. The sub-ethnic groups can be divided based on the region they inhabit; the northern (Melayu Kedah and Melayu Kelantan), western (Melayu Minang) and southern parts (Melayu Bugis and Melayu Jawa) of Peninsular Malaysia. We analyzed 54,794 autosomal single nucleotide polymorphisms (SNPs) which were shared by 472 unrelated individuals from 17 populations to determine the genetic structure and distributions of the ancestral genetic components in five Malay sub-ethnic groups namely Melayu Bugis, Melayu Jawa, Melayu Minang, Melayu Kedah, and Melayu Kelantan. We also have included in the analysis 12 other study populations from Thailand, Indonesia, China, India, Africa and Orang Asli sub-groups in Malay Peninsula, obtained from the Pan Asian SNP Initiative (PASNPI) Consortium and International HapMap project database. Results: We found evidence of genetic influx from Indians to Malays, more in Melayu Kedah and Melayu Kelantan which are genetically different from the other Malay sub-ethnic groups, but similar to Thai Pattani. More than 98% of these northern Malays haplotypes could be found in either Indians or Chinese populations, indicating a highly admixture pattern among populations. Nevertheless, the ancestry lines of Malays, Indonesians and Thais were traced back to have shared a common ancestor with the Proto-Malays and Chinese. Conclusions: These results support genetic admixtures in the Peninsular Malaysia Malay populations and provided valuable information on the enigmatic demographical history as well as shed some insights into the origins of the Malays in the Malay Peninsula.